The Efforts to Align Legal Vacancies in Law Number 4 of 2023 to Strengthen the Independence of the Financial Services Authority in Supervising the Financial Services Sector - Edi Sarwono; Evita Isretno Israhadi (Journal of Social Science, 2024)
The legal gap in Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Services Sector is a significant challenge to the effectiveness of supervision of the Financial Services Authority (OJK) in Indonesia. Issues such as unclear definitions, lack of specific provisions, ambiguity in inter-agency relations, and minimal strict law enforcement have resulted in doubts about the implementation of OJK's duties. To overcome these problems, efforts are needed to harmonize through the formulation of clear definitions, the regulation of more specific provisions, and increased coordination between institutions. In addition, providing law enforcement powers and facilitating the preparation of derivative regulations are also important to strengthen OJK's independence. With these alignment steps, it is hoped that OJK can operate more effectively and contribute to the stability of the financial services sector in Indonesia